Safety and efficacy of non-vitamin K antagonist oral anticoagulants for prevention of thromboembolism in adults with systemic right ventricle: Results from the NOTE international registry. (1st January 2021) - Scognamiglio, Giancarlo; Fusco, Flavia; Hankel, Tara C.; Bouma, Berto J.; Greutmann, Matthias; Khairy, Paul; Ladouceur, Magalie; Dimopoulos, Konstantinos; Niwa, Koichiro; Broberg, Craig S.; Miranda, Berta; Budts, Werner; et al.
Abstract: Background: Patients with systemic right ventricle (sRV), including transposition of great arteries (TGA) after atrial switch procedure and congenitally corrected transposition of great arteries (ccTGA), may require anticoagulation for thromboembolism (TE) prevention. In the absence of data on non-vitamin K antagonist oral anticoagulants (NOACs), vitamin K antagonists (VKAs) remain the agent of choice. We investigated the safety, efficacy and feasibility of NOACs treatment in adults with sRV in a worldwide study. Methods: This is an international multicentre prospective study, using data from the NOTE registry on adults with sRV taking NOACs between 2014 and 2019. The primary endpoints were TE and major bleeding (MB). The secondary endpoint was minor bleeding. Results: A total of 76 patients (42.5 ± 10.0 years, 76% male) with sRV (74% TGA, 26% ccTGA) on NOACs were included in the study. During a median follow-up of 2.5 years (IQR1.5–3.9), TE events occurred in 3 patients (4%), while no MB episodes were reported. Minor bleeding occurred in 9 patients (12%). NOAC treatment cessation rate was 1.4% (95%CI:0.3–4%) during the first year of follow-up. All the patients with TE events had a CHA2 DS2 -VASc score ≥ 2 and impaired sRV systolic function at baseline. The total incidence of major events during follow-up was significantly lower compared to historical use of VKAs or aspirin before study inclusion (1.4% (95%CI:0.29–4%) vs 6, 9% (95%CI:2.5–15.2%); p = .01). Conclusions: In this prospective study, NOACs appear to be well-tolerated, with excellent efficacy and safety at mid-term in patients with sRV. Highlights: NOACs treatment is safe and effective at mid-term in the population with sRV. Discontinuation rate is low at mid-term. Events rate on NOACs is lower compared to vitamin K antagonists or aspirin use. Subjects with impaired sRV function and CHA2 DS2 -VASc≥2 may have higher risk of TE.